Seed Health, Quality Test, and Control of Seed-borne Fungi of Some Improved and Local Cultivars of Rice (Oryza sativa L.) in Kano, Northwestern Nigeria - Edun, Bolanle Tolani; Lurwanu, Yahuza; Sunusi, Mustapha; Sulaiman, Ali A (Department of Agronomy and Horticulture, IPB University, 2019)
This research was carried out to evaluate the health and quality of rice seed. The germination of seed and presence of rice seed related fungi were recorded and used to evaluate the effect of seed dressing chemicals on germination and vigor index over untreated rice seeds. Seven cultivars commonly grown in Kano, Kano State, Northwestern Nigera “FARO 52” (WITA), “FARO 44” (SIPI), “FARO 60” , (improved varieties), “Kwandala” , “Jamila” , Ex-china, and “JIF” (local varieties) were used in this study. The seed dressing chemicals used were Apron Star 42 WS, Dress Force 42WS and ZEB-Care 80%WP. This study was performed under three main tests, i.e dry inspection, blotter tests, agar plate and microscopic examination. The highest number of healthy seeds (94.16%) was recorded from “JIF” variety and lowest (64.77%) from “Jamila” . The highest number of deformed seeds was observed from variety “FARO 44” whereas the lowest noted on “JIF” . The identified fungi were Fusarium spp., Bipolaris oryzae, Aspergillus flavus, Curvularia lunata, Aspergillus niger, and Nigrospora oryzae., Rhizoctonia spp. and Rhizopus spp. Highest seed infection was recorded for A. flavus, A. niger, and Fusarium spp., and the least with C. lunata and N. oryzae. Treated seeds with Zeb-care (Mancozeb 80% WP), increased their vigor index over untreated by 62.78% and can be recommended as seed dressing chemical for optimun control of rice seed- borne pathogens.